In Vitro Evaluation of Antibacterial, Antioxidant, and Antidiabetic Activities and Glucose Uptake through 2-NBDG by Hep-2 Liver Cancer Cells Treated with Green Synthesized Silver Nanoparticles. (17th May 2022) - Majeed, Shahnaz; Danish, Mohammed; Zakariya, Norul Aini; Hashim, Rokiah; Ansari, Mohammed Tahir; Alkahtani, Saad; Hasnain, Md Saquib
Abstract : The alarming rise in diabetes owing to drug resistance necessitates the implementation of prompt countermeasures in the treatment module of diabetes. Due to their unique physicochemical features, silver nanoparticles may have potential applications in the medical and pharmaceutical industries. Silver nanoparticles (AgNPs) were synthesized from the culture filtrate of Salmonella enterica (ATCC-14028). UV-Vis spectrophotometry, FTIR, SEM, and energy dispersive X-rays were used in the characterization of the nanoparticles. Transmission electron microscopy (TEM) revealed that AgNPs are spherical and highly scattered and vary in size from 7.18 nm to 13.24 nm. AgNP stability and protein loss were confirmed by thermogravimetric analysis (TGA) at different temperatures. The AgNPs had excellent antibacterial activity and a strong synergistic effect against methicillin-resistant bacteria Staphylococcus aureus (MRSA) ATCC-4330 and Streptococcus epidermis (MRSE) ATCC-51625. The DPPH experiment revealed that the AgNPs had high antioxidant activity. The antidiabetic assay revealed that these AgNPs had an IC50 for alpha-amylase of 428.60  μ g/ml and an IC50 for alpha-glucosidase of 562.02  μ g/ml. Flow cytometry analysis of Hep-2 cells treated with AgNPs (40  μ g/ml) revealed higher expression of 2-NBDG glucose absorption (uptake) compared to control metformin. These AgNPs have promising antidiabetic properties and could be used in pharmaceuticals and biomedical industries.